(untitled) (Research, Society and Development, 2022)
Polyaniline (PAni) is a conductive polymer with colorimetric properties, which can be combined with biopolymers to form novel composite materials. These materials can be used as a colorimetric sensor/indicator in the identification of different kinds of analytes. The present study aimed to develop a film of PAni and gum Arabic (GA) by electrochemical method to evaluate its potential use in a colorimetric sensor for ammonia vapor (NH3). The composite PAni/GA was prepared by electrochemical polymerization on a gold surface using the cyclic voltammetry technique. The stability of the films was evaluated in acid (HCl 0.1 mol L-1) after 25 imaging cycles. Strongly acidified gum arabic solution (pH 0.0) and a sweep speed of 10 mV s-1 caused higher current density in the film formation. The morphology of the films was observed by SEM and the presence of cracks in its structure can favor the entry of gases. The response of the composite in the presence of NH3 was measured using a colorimeter. The PAni/GA composite is a promising and rapid tool for use in colorimetric sensors in the detection of NH3.